Serological status and associated risk factors of Aujeszky's Disease and Classical Swine Fever in Peninsular Malaysia - Low, Suet Ee (2019)
Aujeszky's Disease (AD) and Classical Swine Fever (CSF) are endemic viral diseases causing great economic impact to the pig industry with limited data about the current disease status in Malaysia. Hence, our study was aimed to determine the serological status of AD and CSF, investigate ADV field challenge and CSF protection, and identify the possible risk factors contributed to the current situation in Peninsular Malaysia swine farms based on commercial samples submitted to UPM during 2016-2017. In this study, convenient sampling method was used and questionnaire was carried out in accessible farms. ELISA test was conducted using IDEXX Pseudorabies Virus gpI Antibody Test Kit for AD and IDEXX Classical Swine Fever Ab ELISA Test Kit for CSF serology diagnosis. Seroprevalence of AD indicates the infection status while seroprevalence of CSF signifies humoral protection status in this study. All tested farms were categorized according to their location into three categories, (northern, central, and southern region). A total number of 71 farms with 2192 serum samples were submitted for AD ELISA test from 2016 to 2017. Overall AD infection rate is 75.87% from the farms in Peninsular Malaysia submitted to UPM within 2016 to 2017. Seroprevalence in 2017 was higher than the year before. Infection was seen more in breeder herd, especially in sows. Findings shown small-scale farms and open-housed system in farms were associated with the increased risk of AD infection when tested with multinomial logistic regression statistical test. For CSF, 58 farms with 2073 samples in total were received from 2016 to 2017. Farm status classification system was developed in our study with the aim to differentiate the CSF serology results into three status categories (ideal, moderate, and less ideal) according to defined criteria. Generally, 44.78% of the farms were categorized as ideal farm status with overall seroprevalence of 71.37%. Highest seropositive farms were obtained from southern region while northern region had the lowest. Significant associations were found in small-scale farms, vaccine brand, and single vaccination with seronegativity. Inversely, vehicle dip and foot dip were significantly related with seropositive of CSF indicating these practices were important in preventing diseases from entering the farm. Based on the findings in our study, current status of AD is stable while current CSF vaccination program is still insufficient to provide ideal humoral protection in Malaysia.